Characterization of insulin-loaded alginate nanoparticles produced by ionotropic pre-gelation through DSC and FTIR studies - Sarmento, Bruno (2006)
Insulin-loaded nanoparticles were prepared by ionotropic pre-gelation of alginate with calcium chloride followed by complexation between alginate and chitosan. The influence of the pH and stoichiometry relationship between polyelectrolytes providing individual particles with a nano-scale size was assessed by photon correlation spectroscopy (PCS) and scanning electron microscopy (SEM). Insulin-polyelectrolyte interactions at varying pH and polyelectrolytes stoichiometry were assessed by differential scanning calorimetry (DSC) and Fourier-transform infrared (FTIR) studies. Individual and smaller sizing nanoparticles, around 800 nm, were obtained at pH 4.7 with an alginate:chitosan mass ratio of 6:1. Thermograms of insulin-loaded nanoparticles originated shifts on same unloaded nanoparticle peaks and suggested polyelectrolytes-protein interactions at pH around 4.5-5.0. FTIR spectra of insulin-loaded nanoparticles showed amide absorption bands characteristic of protein spectra and revealed the formation of new chemical entities.